Problematika Penegakan Hukum Pidana Terhadap Pelaku Penyerobotan Tanah Perspektif Hukum Pidana dan Hukum Islam di Wilayah Hukum Polda Jambi - Amri, Yusrizal; Halim, Abdul; Ramlah, Ramlah (Journal of Law, Education and Business, 2025)
This research aims to find out and analyze the problems of criminal law enforcement against land grabs from the perspective of criminal law and Islamic law and the factors that hinder the process of investigating land grabs in the Jambi Regional Police jurisdiction. The research method is a qualitative method, while the type of research is library research. The research was carried out by the author collecting secondary data obtained from books and writings related to the theme. The results of this research indicate that the problem of law enforcement in cases of land grabbing in the Jambi Regional Police's jurisdiction is hampered by the existence of PERMA Number 1 of 1956 which states that in the investigation of a criminal case, a decision must be made regarding the existence of a civil matter or an item or regarding a legal relationship between two certain parties. Then the criminal case examination can be postponed to wait for a court decision in the civil case examination regarding the existence or non-existence of civil rights. Meanwhile in Islamic law the issue of land grabbing has not been discussed in detail but the closest term is gasab (utilizing other people's rights without the permission of the owner and carried out openly), in carrying out their duties the police also encounter several obstacles, such as obstacles that include internal police, namely where infrastructure and so on, and external obstacles caused by the community itself and this is very crucial in investigating this matter, namely administrative matters (land titles), in enforcing criminal acts, it is hoped that Jambi Regional Police investigators carry out their duties in a professional manner with the aim of assisting and speeding up the investigation process in handling a case of encroachment.